Nano-MIP based SPR sensor for tetracycline analysis in milk sample - Monireh Bakhshpour-Yücel; Melike Küçük; Elif Tümay Özer; Bilgen Osman (Talanta Open)
Recent advancements in sensor technology have enabled the detection of antibiotics in food, ensuring human safety. In this study, we developed a surface plasmon resonance (SPR) sensor based on molecularly imprinted nanoparticles (MINps) for the real-time, sensitive, and in-situ detection of tetracycline (Tc). Firstly, Tc-imprinted nanoparticles (Tc-MINps) were synthesized using microemulsion polymerization. Then, the Tc-MINps were coated onto a bare gold SPR chip to develop the Tc-MINps SPR sensor. The sensor's performance was evaluated by detecting Tc in aqueous solutions. The results demonstrated a highly selective binding of Tc to the nanocavities on the surface of the Tc-MINps SPR sensor. The relationship between Tc molecules and the SPR sensor was analyzed at 0.5–20 mg/L Tc concentrations (pH 5.0). The Langmuir isotherm model was identified as the most appropriate binding model, indicating monolayer adsorption. The selectivity of the Tc-MINps SPR sensor was investigated using oxytetracycline, ciprofloxacin, and amoxicillin due to their structural similarity. The selectivity coefficients were determined as 5.54 for oxytetracycline, 23.66 for ciprofloxacin, and 28.39 for amoxicillin. Additionally, the limit of detection (LOD) for the Tc-MINps SPR sensor for Tc analysis in milk was found to be 0.45 mg/L, while the LOD for the HPLC method was 0.55 mg/L. The developed SPR sensor is suitable for Tc detection in milk due to its advantages, such as real-time monitoring, low cost, high selectivity, and reusability.